(untitled) (The Agriculturists, 2010)
In the context of global energy crisis and water scarcity, rice production system is undergoing changes with the strategy to produce more rice with lesser amount of water. Water saving technology has therefore, been developed and increasingly adopted to irrigate rice in different countries. Impact of alternate wetting and drying (AWD) irrigation as a water saving technique on rice yield, water productivity and environment has been overviewed in this paper. On-farm trials were conducted during the years 2007 and 2008 to validate the adaptability of AWD method of irrigation in Boro rice-variety BRRI dhan29. The trials were conducted at different locations of Gazipur, in which three farmers plots of rice were irrigated following AWD method, which were then compared with another 3 farmers plots of rice irrigated in conventional method maintaining 3-5 inches of standing water throughout. The trials have revealed that AWD method saved about 365 mm irrigation water (about 27%) over the conventional irrigation practice. However, there was no adverse effect of AWD- irrigation on grain yields of rice. AWD method as perceived by farmers, although reduced irrigation cost, resulted in more weed infestation and was associated with more weeding cost. Following the impressive results of the validation trials, the demonstrations were conducted in the farmers fields of different districts during boro 2009. In general, the demonstrations were successful to impress the farmers about AWD-irrigation as a water saving and low-cost irrigation method. However assurance of timely availability of irrigation is a precondition for farmers to adopt the technique and weed management using appropriate herbicides is necessary for adoption of the technology.